2014
DOI: 10.1117/12.2047255
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial polyelectrolyte-coated Mg alloys for biomedical applications

Abstract: This study deals with two biomedical subjects: corrosion rates of polyelectrolyte-coated magnesium (Mg) alloys, mainly used for biomedical purposes, and antibacterial properties of these alloys. Thin sheets of Mg alloys were coated with cationic polyelectrolyte chitosan (CHI) and anionic polyelectrolyte carboxymethyl cellulose (CMC) using a layer-by-layer coating method and then embedded with antibacterial agents under vacuum. Electrochemical impedance spectroscopy was employed to analyze these samples in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The characteristics of ideal scaffolds for bone tissue engineering include the following: (1) interconnecting pores, including both macropores (pore size > 100 μm) and micropores(pore size < 20 μm) for tissue growth, substance transplantation, and vascularization; (2) biodegradable or bioabsorbable materials with strong mechanical properties to transfer load to the surrounding tissue; and (3) a good scaffold interface to adhere, proliferate, and differentiate cells efficiently (Saiz et al 2013; Bose et al 2012). Various materials, including biodegradable polymers such as polycaprolactone (PCL), polylactide (PLA), polyorthoester (POE), polyglycolide or polyglycolic acid (PGA), and their copolymers poly (lactic- co -glycolide) (PLGA) have been used to fabricate scaffolds, which could provide initial support and mechanical strength with adequate porosity for cell attachment (Seal et al 2011; Mano et al 2014; Seraz et al 2017; Asmatulu et al 2019). Thus, in the past few years, the combination of polymer/ceramic composites has gained much interest in the field of tissue engineering (Zanello et al 2016; Abedin et al 2015; Uddin et al 2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of ideal scaffolds for bone tissue engineering include the following: (1) interconnecting pores, including both macropores (pore size > 100 μm) and micropores(pore size < 20 μm) for tissue growth, substance transplantation, and vascularization; (2) biodegradable or bioabsorbable materials with strong mechanical properties to transfer load to the surrounding tissue; and (3) a good scaffold interface to adhere, proliferate, and differentiate cells efficiently (Saiz et al 2013; Bose et al 2012). Various materials, including biodegradable polymers such as polycaprolactone (PCL), polylactide (PLA), polyorthoester (POE), polyglycolide or polyglycolic acid (PGA), and their copolymers poly (lactic- co -glycolide) (PLGA) have been used to fabricate scaffolds, which could provide initial support and mechanical strength with adequate porosity for cell attachment (Seal et al 2011; Mano et al 2014; Seraz et al 2017; Asmatulu et al 2019). Thus, in the past few years, the combination of polymer/ceramic composites has gained much interest in the field of tissue engineering (Zanello et al 2016; Abedin et al 2015; Uddin et al 2019a, b).…”
Section: Introductionmentioning
confidence: 99%
“…In case of polyelectrolyte-coated samples (Figure 9), the interaction between the polyelectrolytes and the antibacterial drugs used could be a reason for the weaker antibacterial function of the polyelectrolyte-coated samples loaded with combination drugs. It is clearly concluded that incorporation of chitosan into gentamicin-loaded bone cement for use in joint replacement surgery has no antimicrobial benefit and the detrimental effect on mechanical properties may have an adverse effect on the longevity of the prosthetic joint [25]. It has been investigated whether the incorporation of chitosan in gentamicin-loaded bone cement increases antibiotic release, and prevents bacterial adherence and biofilm formation by clinical isolates of Staphylococcus spp.…”
Section: Antibacterial Sensitivity Testsmentioning
confidence: 99%
“…Bioresorbable scaffolds, i.e., porous constructs, seeded with appropriate types of cells should provide a template for tissue regeneration, while slowly resorbing to leave no foreign substances in the body and thereby reducing the risk of inflammation. In the past few years, polymer/carbon-based composites have gained increasing interest in the field of tissue engineering [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%